c-Jun N-terminal kinase activation has a prognostic implication and is negatively associated with FOXO1 activation in gastric cancer - Choi, Youngsun (BMC Gastroenterol, 2016)
BACKGROUND: Since the biological function of c-Jun N-terminal kinase (JNK) in gastric cancer remains unclear, we investigated the clinical significance of JNK activation and its association with FOXO1 activation. METHODS: Immunohistochemical tissue array analysis of 483 human gastric cancer specimens was performed, and the results of the immunostaining were quantified. The correlation between JNK activation (nuclear staining for pJNK) and clinicopathological features, the proliferation index, prognosis or FOXO1 inactivation (cytoplasmic staining for pFOXO1) was analyzed. The SNU-638 gastric cancer cell line was used for in vitro analysis. RESULTS: Nuclear staining of pJNK was found in 38 % of the gastric carcinomas and was higher in the early stages of pTNM (P < 0.001). pJNK staining negatively correlated with lymphatic invasion (P = 0.034) and positively correlated with intestinal type by Lauren’s classification (P = 0.037), Ki-67-labeling index (P < 0.001), cyclin D1 (P = 0.045), cyclin E (P < 0.001) and pFOXO1 (P < 0.001). JNK activation correlated with a longer patients survival (P =0.008) and patients with a JNK-active and FOXO1-inactive tumor had a higher survival rate than the remainder of the population (P = 0.004). In vitro analysis showed that JNK inhibition by SP600125 in SNU-638 cells decreased cyclin D1 protein expression and increased FOXO1 activation. Further, JNK inhibition markedly suppressed colony formation, which was partially restored by FOXO1 shRNA expression. CONCLUSIONS: Our results indicate that JNK activation may serve as a valuable prognostic factor in gastric cancer, and that it is implicated in gastric tumorigenesis, at least in part, through FOXO1 inhibition.